From collective health to “personalized” medicine: bioethical challenges in preimplantation genetic testing from a North-South perspective = From collective health to “personalized” medicine: bioethical challenges in preimplantation genetic testing from a North-South perspective - Lima, Natacha Salomé; Petino Zappala, María Alejandra; Delvitto, Ailin; Romero, Miguel Adrián; Pallitto, Nahuel (Salud colectiva, 2023)
This article examines the scope and limitations of the precision medicine paradigm and its relationship with the collective health approach. To that end, it takes preimplantation genetic testing (PGT) as a paradigmatic example of technologies aimed at the “individualization” of health processes. In this regard, we review the characteristics and scientific and regulatory foundations of PGT technologies in Argentina, and discuss the next steps for their bioethical analysis. More specifically, we shed light on some of the conditions for their implementation from a north-south perspective. We propose three themes or problematic aspects as a synthesis of our analysis, related to biases in the production of knowledge, the values and interests underlying its uses, and the underlying epistemological assumptions of these technologies. Throughout the article, we review these dilemmas and suggest some issues that should be taken into account in future research.
Gesehen am 09.02.2026